Effects of Cocaine and Fasting on the Intake of Individual Macronutrients in Rats - Mitchell, Nia; Roseberry, Aaron G. (Frontiers in Neuroscience, 2019)
Obesity is a significant problem, and increased food intake is thought to underlie much of the increase in obesity levels. Recently, there has been much discussion and debate about the role of the individual macronutrients, carbohydrates, fat, and protein, in the rise in obesity levels and its associated comorbidities, but overall there has been little study of how different treatments and stimuli that affect feeding impact the intake of individual macronutrients. In these studies, we tested whether two treatments leading to altered feeding, acute cocaine injection and an acute fast, differentially affect the intake of individual macronutrients using a three diet choice paradigm. Cocaine strongly inhibited the intake of each individual test diet (carbohydrate, fat, and protein), but there were no differences between its effects on the intakes of each individual diet. In contrast, an acute fast had little effect on the intake of any of the diets and did not differentially affect the intake of the three test diets. Thus, these studies demonstrate that cocaine can effectively inhibit the intake of feeding independent of its macronutrient content, and significantly advance our understanding of the neural regulation of individual macronutrient intake.